Mycotoxins : detection methods, management, public health, and agricultural trade - Mycoglobe Conference "Reducing Impact of Mycotoxins in Tropical Agriculture" (2005 : Accra, Ghana); Leslie, John F., 1953-; Bandyopadhyay, Ranajit, 1953-; Visconti, Angelo; C. A. B. International (Wallingford, UK ; Cambridge, MA ; Cambridge, MA : CABI)
Includes bibliographical references and index